2019
DOI: 10.1530/ec-19-0199
|View full text |Cite
|
Sign up to set email alerts
|

Altered methylation pattern of the SRD5A2 gene in the cerebrospinal fluid of post-finasteride patients: a pilot study

Abstract: Context Post-finasteride syndrome (PFS) occurs in patients with androgenic alopecia after suspension of the finasteride treatment, leading to a large variety of persistent side effects. Despite the severity of the clinical picture, the mechanism underlying the PFS symptoms onset and persistence is still unclear. Objective To study whether epigenetic modifications occur in PFS patients. Methods Retrospective analysis of a multicentric, prospective, longitudinal, case–control clinical trial, enrolling 16 PFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Several studies (69,73,74,127,149) reported that depressive symptoms were significantly more prevalent in finasteride users than in non-users and the incidence of moderate to severe depressive symptoms were higher in the finasteride treated patients than in non-users. Suicidal thoughts were declared in 44% of the former finasteride users and only in 3% of the controls (62,69,73,74,75). An analysis of the FDA database (FEARS) revealed persistent suicidal ideation in 7.9% of males (127).…”
Section: Debruyne Et Al 2004 (106)mentioning
confidence: 98%
“…Several studies (69,73,74,127,149) reported that depressive symptoms were significantly more prevalent in finasteride users than in non-users and the incidence of moderate to severe depressive symptoms were higher in the finasteride treated patients than in non-users. Suicidal thoughts were declared in 44% of the former finasteride users and only in 3% of the controls (62,69,73,74,75). An analysis of the FDA database (FEARS) revealed persistent suicidal ideation in 7.9% of males (127).…”
Section: Debruyne Et Al 2004 (106)mentioning
confidence: 98%
“…There is some evidence for penile curvature or other penile effects in men with PFS [ 25 ], but it is not clear if this was present prior to treatment or has resulted since. Alterations in neuroactive steroid levels [ 34 ], methylation of 5 alpha-reductase type 2 in cerebrospinal fluid [ 35 ], and gut microbiota population [ 36 ] have also been found in PFS patients. But again, it is not clear whether these were present before treatment.…”
Section: Post-finasteride Syndrome (Pfs)mentioning
confidence: 99%
“…On the other hand, it is important to highlight that observations obtained in PFS patients and in male rats after finasteride suspension show the nervous system as an important target, with alterations that could be associated with sexual dysfunction, such as depressive symptomatology and peripheral neuropathy. 7,20,27,28,32,45 In addition, it is important to remember that male sexual behavior (e.g., sexual motivation and reward to sexual performance) is under the control of complex neural circuits. 1,52 Therefore, future experiments will be important to explore whether finasteride withdrawal affects these circuits and molecules involved, such as neurotransmitters and neuropeptides.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Interestingly, these side effects may persist after the drug suspension, inducing the so-called post-finasteride syndrome (PFS). 9,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] The effects of finasteride treatment were also reported in animal models. For instance, finasteride treatment in castrated rats decreased erectile response, although receiving T replacement 35,36 and in control male rats, it decreased intracavernosal pressure during electrical stimulation of cavernous nerves.…”
Section: Introductionmentioning
confidence: 97%